Evolutionary features of subsurface defects of single crystal diamond after dynamic friction polishing - Sheng Ye; Yuting Zheng; Shangman Zhao; Jinlong Liu; Liangxian Chen; Haitao Ye; Xiaotong Zhang; Xiaoping Ouyang; Chengming Li; Junjun Wei (Functional Diamond, 2024)
Due to the fatigue and continuous energy input during high-speed dynamic friction polishing (DFP), the diamond crystal beneath the polished surface (roughness <1 nm) can be distorted/cracked in varying degrees by adjusting the polishing process. In this study, the local amorphization, dislocation extension, and subsurface cleavage with the prolonging of sliding duration were examined in the nanoscale. Different to the localized distortion with sp2-π* states in the near-surface area (<10 nm) after 15 min DFP, continuous mechanical friction would give rise to the dislocation penetration (to >50 nm) and even preferential crystal cleavage with the non-diamond phase (distributing at the position in micrometers range).